Flavonoids from Lycium barbarum leaves attenuate obesity through modulating glycolipid levels, oxidative stress, and gut bacterial composition in high-fat diet-fed mice - Liao, JiaLe; Guo, Jia; Niu, YinHong; Fang, Tian; Wang, FangZhou; Fan, YanLi (Frontiers in Nutrition, 2022)
Lycium barbarum leaves as traditional herbal medicine has been reported to exert vital roles in the amelioration of metabolic disorders, but its specific mechanisms remain unclear. The natural flavonoids had been regarded as a safe and effective approach to the management of obesity. Therefore, we attempted to explore the inhibitory mechanisms of flavonoids from Lycium barbarum leaves (LBLF) on obesity. The obese model mice established by high-fat diet were used to evaluate the intervention efficacy after intragastric administration of different doses of LBLF (50, 100, 200 mg/kg∙bw). LBLF treatment could obviously result in reduction of the body weight increase, lee´s index, serum lipids levels, oxidative stress levels, and hepatic lipids levels as well as increase of the excretion of fecal lipids, and also improve glucose tolerance. Moreover, LBLF treatment effectively reversed HFD-caused gut dysfunction by increasing α-diversity, reducing β-diversity, and altering the gut bacterial community structure with increased probiotics, and depleted pathogenic bacteria.